Groundwater Physicochemical Characteristics’ Analysis of Chicú River Basin, Colombia, Using Hydrochemical Indicators and Multivariate Statistics (2018)
The hydrochemical characteristics of an intramontane basin, located in the Bogotá Savannah, were evaluated using indicators and statistical methods, based on 10 monitoring wells physicochemical data, obtained during two sampling campaigns conducted in 2014, to establish the hydrochemical characteristics that are generated by the groundwater and sedimentary matrix interaction of the aquifer and determine the extracted groundwater quality conditions’ in the studied aquifer. To analyze the data, (1) hydrochemical indicators were applied to evaluate the groundwater and the sedimentary matrix interaction processes’ in the studied aquifer, which was corroborated by (2) principal components analysis, which allowed to disclose strong associations between the variables (Na+, Mg2+, Ca2+, SO42- y HCO3-), and T, pH y TDS variables influence on the hydrochemical process that govern the analyzed aquifer, in addition (3) physicochemical parameters were compared with the Colombian environmental regulations, referring to human consumption and irrigation use. As results, in water-sediment matrix was determined reverse cation exchange and minerals meteorization processes, present in the formations that conform the analyzed aquifer, likewise, the water samples obtained do not present quality characteristics that allow its use for irrigation or human consumption.